Development and evaluation of sustained release matrix tablets of ketoprofen employing natural polymers (pomegranate peel and acacia powders) - Al-Pokhiti, Mohammad; Al-Tahami, Khaled (Journal of Chemical and Pharmaceutical Research, 2016)
In the present study, we developed sustained release matrix tablets of ketoprofen using natural polymers (pomegranate peel and acacia powders) in different formulations. The tablets prepared by wet granulation method were subjected to evaluation for pre-compression parameters including: bulk density, tapped density, compressibility(Carr's index) and Hauser's ratio. Also, the prepared tablets were subjected to evaluation for post - compression parameters including: weight variation, drug content, hardness and friability tests. All physical characters of fabricated tablets were within the acceptable limits of pharmacopoeia. In vitro release studies showed that different formulations exhibited sustained release of ketoprofen over ten hours period. It was concluded that the used polymers (pomegranate peel and acacia powders) can be used as sustained release matrix tablet to provide sustained release of ketoprofenin order to extend the duration of its action, reduce the frequency of dosing and increase patient compliance.